Assessing food waste and environment-related factors: Evidence from urban households in Southwestern Nigeria (International Journal of Sustainable Development & World Policy, 2025)
This study assessed food waste and environment-related factors among urban households in Southwestern Nigeria. The objectives were to identify commonly wasted food types, examine household practices and attitudes toward food storage, consumption, and waste disposal, and analyze the socio-economic, cultural, and environmental determinants of food waste. A multistage sampling technique was used to select 240 respondents, and data were collected using structured questionnaires. Descriptive statistics and multiple regression analysis were employed to analyze the data. Results revealed that commonly wasted foods include legumes, noodles, bread, and cereals, largely due to over-purchasing, convenience preferences, and short shelf life. Perception analysis showed general awareness of food waste, although some households still engage in wasteful practices. Environmental factors such as inadequate municipal waste collection and irregular electricity supply significantly contribute to household food spoilage. Regression analysis indicated that variables including household income, the presence of children under 10 years old, access to refrigerators, frequency of food purchases, and environmental awareness substantially influence the level of food waste. The study concluded that food waste in urban households is a complex issue shaped by socio-economic, behavioral, and environmental factors. It recommended implementing awareness campaigns, improving infrastructure for food preservation, and developing targeted policy interventions to promote sustainable household food management and mitigate the negative environmental impacts of food waste.